AESTHETIC ANALYSIS OF FORMS IN SMART CASUAL WEAR “KSATRIA WASTRA AVIRAMA” - Dewa Ayu Putu Leliana Sari; Ida Ayu Kade Sri Sukmadewi; I Gusti Bagus Priatmaka (Yayasan Sinergi Widya Nusantara, 2022)
Purpose : This study aims to know the aesthetic analysis of the shape of the smart casual fashion work of Ksatria Wastra Avirama. Research methods: this research uses qualitative methods, The data were collected through observation, documentation, and literature, then the data were analyzed using descriptive qualitative methods. Findings: Ksatria Wastra Avirama is a fashion collection consisting of 5 pieces of smart casual clothing made from endek patchwork and seseh woven fabrics. The process of doing work using textile manipulation techniques. Each outfit has a special meaning based on the collected patchwork colors. The aesthetics of the analyzed form are elements of art and design principles in clothing. Implications: The results show: The aesthetics of form in the work of Ksatria Wastra Avirama were formed from artistic elements in the form of horizontal, vertical, and diagonal lines, pant silhouettes, square and triangular shapes, and different colors for each design (red, yellow-brown, blue-purple, black and blue, and green), hairy texture, stiff and matte, the size uses the